1994
DOI: 10.1210/endo.135.5.7525252
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide: an autocrine regulator of human granulosa-luteal cell steroidogenesis.

Abstract: We investigated the presence of nitric oxide (NO) synthase in ovarian follicular cells obtained from women undergoing in vitro fertilization procedures. Endothelial NO synthase messenger RNA was demonstrated by polymerase chain reaction amplification of reverse transcribed RNA. NO synthase was localized to granulosa-luteal cells by immunocytochemistry, using a monoclonal antibody. Ovarian follicular cell NO synthase enzyme activity was confirmed by measuring the conversion of L-arginine to citrulline. To inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(72 citation statements)
references
References 24 publications
9
60
0
Order By: Relevance
“…This finding could be related to the decrease of plasmatic estradiol observed in these rats, in agreement with findings of other authors who showed that the iNOS localized in granulosa cells was highly expressed when the steroidogenesis was virtually absent (18). The NO rise was inversely proportional to the levels of progesterone, similar to the report showing a concentration-dependent inhibition of progesterone synthesis in the presence of the NO donors (2) suggesting that the generated NO might be able to inhibit steroidogenesis and mediate the cytotoxic actions of IL-1 pon ovarian cells (17). In the present work, the addition of cx-MSH reverted the effect of EAO, indicating that NO release diminished and progesterone levels augmented in estrus rats before and after the constant diestrus period.…”
Section: Discussionsupporting
confidence: 86%
“…This finding could be related to the decrease of plasmatic estradiol observed in these rats, in agreement with findings of other authors who showed that the iNOS localized in granulosa cells was highly expressed when the steroidogenesis was virtually absent (18). The NO rise was inversely proportional to the levels of progesterone, similar to the report showing a concentration-dependent inhibition of progesterone synthesis in the presence of the NO donors (2) suggesting that the generated NO might be able to inhibit steroidogenesis and mediate the cytotoxic actions of IL-1 pon ovarian cells (17). In the present work, the addition of cx-MSH reverted the effect of EAO, indicating that NO release diminished and progesterone levels augmented in estrus rats before and after the constant diestrus period.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, the inhibition of testosterone secretion by NO is also established (Adams et al 1994;Welch et al 1995). Moreover, NO is known to inhibit estradiol secretion by human granulosa-luteal cells by directly inhibiting aromatase, the enzyme responsible for the conversion of androgens to oestrogens (Van Voorhis et al 1994). In this connection it was shown that Sertoli cells and Leydig cells of different species express P-450 aromatase (Fitzpatrick and Richards 1993;Saez 1994).…”
Section: Discussionmentioning
confidence: 97%
“…We thus presume that the cells can produce NO which may act in an autocrine or paracrine fashion to influence their activity, or that of peritubular and tunica albuginea myofibroblasts, or vascular smooth muscle cells (Davidoff et al 1995). Recent evidence also suggests that NO may influence testosterone synthesis in Leydig cells (Adams et al 1992(Adams et al , 1994Welch et al 1995) and estradiol secretion in human granulosa-luteal cells (Van Voorhis et al 1994). Moroever, female steroid sex hormones modulate the production of NO in the rat uterus (Yallampalli et al 1994) and androgens differentially affect NOS activity in the reproductive tract of male rats (Chamness et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Among monovulatory species, NOS expression has been scarcely investigated in humans but eNOS was demonstrated within granulosa-lutein cells (Van Voorhis et al 1994).…”
Section: Regulation Of No Productionmentioning
confidence: 99%
“…As sex steroids play an important role in the growth and differentiation of reproductive tissues, different factors that impair their production usually compromise fertility. NO has been demonstrated to inhibit follicular steroidogenesis in rats (Dave et al 1997, Shahpar et al 2007, human (Van Voorhis et al 1994, Rosselli et al 1998, Tobai & Nishiya 2001, bovine (Basini et al 1998, Faes et al 2009), buffalo (Dubey et al 2011), and swine (Masuda et al 1997, Matsumi et al 2000, Grasselli et al 2001. NO exerts its effects by binding to the prosthetic heme group of enzymes.…”
Section: Role Of No In the Control Of Follicular Steroidogenesismentioning
confidence: 99%